Rational selection of reverse phase columns for high throughput LC–MS lipidomics. (July 2019) - Criscuolo, Angela; Zeller, Martin; Cook, Ken; Angelidou, Georgia; Fedorova, Maria
Highlights: Human blood plasma lipidome analyzed by reverse-phase LC–MS. Comparison of RPC columns with different stationary phases. Rational selection of stationary phase based on the lipidome complexity. More than 640 lipid molecular species identified in blood plasma. Abstract: Natural lipidomes are characterized by extremely high complexity and dynamic range of lipid concentrations. Furthermore, high diversity of lipid physicochemical properties requires high resolving powers for both chromatographic and mass spectrometric analytical platforms. Reverse-phase chromatography coupled with data-dependent MS/MS acquisition is one of the most popular techniques in untargeted lipidomics. Optimal method should provide good chromatographic separation and resolution, reproducibility, selectivity and sensitivity. Here, we developed and set-up a RPLC-MS/MS workflow capable of resolving complex mixtures of lipids in 32 min of analysis. Human blood plasma was chosen as a representative complex natural lipidome with large variance of lipid classes, species and lipid concentrations. Lipids were separated by RPLC on five different reverse phase columns with different types of stationary phase particles, size and chemistry. High mass accuracy MS analysis and data-dependent MS/MS analysis were performed using a Q Exactive™ HF Hybrid Quadrupole-Orbitrap™ Mass Spectrometer to identify individual lipid molecular species. This workflow was applied to evaluate the separation capability of each column and to identify the lipidomics profile in highly complex biological samples. As a result, we report more than 600 lipid species covering 18 lipid classes in human blood plasma and provide suggestions to the selection of the appropriate reverse phase column for the analysis of specific lipidomes.